2006
DOI: 10.1111/j.1467-9663.2006.00363.x
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Measurement of Regional Culture in the Netherlands

Abstract: Culture is a key concept in contemporary cultural and economic geography, but geographical research on culture is thus far mainly limited to case studies. To supplement this qualitative approach with a quantitative analysis of cultural causes and effects of geographic phenomena a data set is needed that somehow measures culture. This paper presents an attempt at such a measurement at the spatial scale of Dutch municipalities. Culture as a 'map for behaviour' is measured here indirectly, by means of factor anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 42 publications
1
36
0
1
Order By: Relevance
“…As a consequence of the 'urban culture', living in urban areas may nurture new value orientations and open-mindedness, leading to larger networks of friends and acquaintances and increasing opportunities to meet partners in a greater range of meeting places, distributed in a greater area, thus widening the distance to partners. For the Netherlands, Brons (2006) studied dimensions of regional culture and found considerable regional variation in value orientations. His measurement of value orientations is derived from indirect measures of demographic behaviour, religious adherence, and voting behaviour, and it is based on Hofstede's (1980Hofstede's ( , 1991 measurement of national cultures.…”
Section: The Spatial Dimension Of Partner Choice: Background and Expementioning
confidence: 99%
See 4 more Smart Citations
“…As a consequence of the 'urban culture', living in urban areas may nurture new value orientations and open-mindedness, leading to larger networks of friends and acquaintances and increasing opportunities to meet partners in a greater range of meeting places, distributed in a greater area, thus widening the distance to partners. For the Netherlands, Brons (2006) studied dimensions of regional culture and found considerable regional variation in value orientations. His measurement of value orientations is derived from indirect measures of demographic behaviour, religious adherence, and voting behaviour, and it is based on Hofstede's (1980Hofstede's ( , 1991 measurement of national cultures.…”
Section: The Spatial Dimension Of Partner Choice: Background and Expementioning
confidence: 99%
“…His measurement of value orientations is derived from indirect measures of demographic behaviour, religious adherence, and voting behaviour, and it is based on Hofstede's (1980Hofstede's ( , 1991 measurement of national cultures. For our study, three dimensions identified by Brons (2006) are pertinent: post-materialism, classic individualism, and Protestant conservatism (see Table 1). These dimensions of regional culture are expected to have an impact on spatial homogamy.…”
Section: The Spatial Dimension Of Partner Choice: Background and Expementioning
confidence: 99%
See 3 more Smart Citations